Globalization as Cultural Imperialism: A Death Knell for the Development of the Indigenous Peoples’ Culture in Africa - IBIAM, Okechukwu Egwu; OKECHUKWU, Groupson-Paul; AGUDIEGWU, Moses Ogbonna; IBE, Emmanuel Chukwuemeka (Socialscientia: Journal of Social Sciences and Humanities, 2022)
Globalization re-defined from a radical ideological perspective is the elevation of cultural imperialism, the highest stage of capitalism; to a global level for multiple vested interests that focuses on the deliberate expropriation of the wealth of weaker nations in the interest of the metropolis. It is posited here that following the decades of metropolitan bourgeois exploitation of Africa, a consistent argument against the vagaries of globalization in the continent, remains that it constitutes a process for stealthy metropolitan expropriation of weak nations by the metropolis in many guises. This is definitively interpreted as liberalist scholars’ knee jerk efforts at justifying further capitalist penetration of the backward societies to create a new world order to benefit the developed nations, while Africa and the other poor nations of the globe continue to wallow in abject poverty. Accordingly, this paper posits that as much as Africans may have bought the dummy for too many times, believing that globalization is the integration of nations of the world into one huge laissez-faire moderated market system, we also argue that it is in part cultural imperialism, methodically rooted in the re-incarnation of the relics of extreme ruthless aggressive ideological war fare for African expropriation. Beyond the fallacies about the benefits of globalization, the truth remains that it is a hydra-headed monster that is spewing economic poisonous ivy to ossify liberalists’ four cardinal objectives of African exploitation, anchored on modern day slavery, neo-colonialism, internationalization of brigandage among the African ruling class and cultural imperialism. This paper is therefore a wakeup call on Africans to rise to the challenges posed by cultural imperialism, by raising questions about globalization, through concerted efforts aimed at creating new forms of political, socio-economic and cultural re-invigoration. It is a call to duty for Africans to take back the dying soul of their culture and ways of life. Nothing short of Africa’s cultural renaissance is the panacea to the orgy of rapacious rape of the minds of Africans through a globalized imperialist debasing of the continent. Africa must initiate home grown mitigations that can foster disciplined resources management, self-reliance and self-help to re-position Africa for greater development.